USEFUL ASSUMPTION FOR SIMPLIFIED NUMERICAL ANALYSIS OF TRANSCRANIAL MAGNETIC STIMULATION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Magnetic stimulation is a bioelectromagnetic effect of exposing the human body to a time-varying magnetic field; excitable tissues (nerves, muscles, sensory organs) can be activated by the electric field (or associated electric current) generated by electromagnetic induction. The biological effects of stimulation have medical applications in a dynamic class of neuromodulation techniques, such as transcranial magnetic stimulation. However, hazardous human exposure to low-frequency, high-amplitude magnetic fields may also be associated with an increased incidence of health risks, as observed in specific occupational exposure scenarios. This study presents some typical issues related to the numerical simulation of electromagnetic field problems in this class (formulation, data, methods, implementation, accuracy), provides specific quantitative estimates (postprocessing of electromagnetic solutions), and illustrates the practical possibility of reducing the consumption of computational resources by adopting a simplified problem description that replaces a transient analysis with a time-harmonic analysis.
Keywords: Transcranial magnetic stimulation (TMS); Inductor current; Numerical analysis; Finite element method (FEM)